DIGITAL TRANSFORMATION IN PARLIAMENTARY INSTITUTIONS: A MULTI-DIMENSIONAL ANALYSIS OF SRIKANDI IMPLEMENTATION AND ITS IMPACT ON INFORMATION MANAGEMENT EFFECTIVENESS - Ariawan, Ariawan; Soemartono, Triyuni; Effendy, Khasan; Sukmana, Pandji (Media Mahardhika, 2025)
This study examines the implementation of digital transformation policy through the Integrated Dynamic Archival Information System (SRIKANDI) at Indonesia's House of Representatives (DPR RI), employing a comprehensive multi-dimensional analytical framework. Using qualitative methodology with case study design, data were collected through in-depth interviews with 25 key stakeholders, participatory observation over six months, and extensive documentation analysis. The research applies Edward III's policy implementation model, DeLone and McLean's information systems success model, and Lewin's organizational change theory to analyze the complex dynamics of digital transformation in parliamentary institutions. Findings reveal that SRIKANDI implementation achieved significant improvements in archival efficiency (67% reduction in document retrieval time) and transparency (85% increase in digital document accessibility), while facing substantial challenges in organizational culture adaptation and technical infrastructure limitations. The study identifies four critical success factors: leadership commitment intensity, digital literacy enhancement programs, infrastructure robustness, and change management strategies. Results demonstrate that successful digital transformation in legislative institutions requires synchronized alignment of policy frameworks, technological capabilities, organizational readiness, and human resource development. This research contributes to the growing literature on e-governance in developing countries and provides actionable insights for parliamentary digital transformation initiatives globally.